Youth, technology, governance, experience adults understanding young people - Grealy, Liam; Driscoll, Catherine; Hickey-Moody, Anna 1977- (Routledge, 2018)
"How far do adults truly understand youth? How do their conceptions inform interventions into young lives or implicate young peoples experiences?Centrally exploring adults ideas about youth, Youth, Technology, Governance, Experience seeks to tackle these questions. Specifically, this timely volume uses the four central concepts of youth, technology, governance and experience to examine a range of relationships that exist between adults and youth including those within homes and educational institutions, government bureaucracies, online, via media representations and new technologies; and elsewhere in everyday life. Topics such as media classification, surveillance, sexting, tertiary education, and health provision are approached using a range of disciplines and methods, including survey and ethnographic interviews, action research, policy, archival and textual analysis, and critical theory. The collections key concepts youth, technology, governance, and experience provide connecting themes across the essays, while also considered on their own terms and with regard to their implications for how we interact with young people. Readers can expect analyses of young people differentiated by gender, class, race, and geography across a range of sites, with attention also given to dominant ideas about and expectations of youth and their varied effects."--Provided by publisher
Keywords: Youth; Information technology; Intergenerational relations